2014
DOI: 10.1680/geng.13.00097
|View full text |Cite
|
Sign up to set email alerts
|

Shear strength of tyre chip–sand and tyre shred–sand mixtures

Abstract: Mixtures of shredded tyres with sand have become accepted geo-materials in the past decade, especially for use as fill materials. Owing to the large size of tyre shreds commonly used in practice, large-scale direct shear testing equipment is specially fabricated to obtain the shear strength parameters of mixtures. The effect of tyre shred-to-sand mixing ratio on the mechanical response of the mixtures is studied by performing direct shear tests on mixtures prepared at different mixing ratios. Out of the four t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Granulated tire sizes according to ASTM D6270-17 [24]. * Balunaini [28], ** Mashi . Granulated tire sizes according to ASTM D6270-17 [24].…”
Section: Methodsmentioning
confidence: 99%
“…Granulated tire sizes according to ASTM D6270-17 [24]. * Balunaini [28], ** Mashi . Granulated tire sizes according to ASTM D6270-17 [24].…”
Section: Methodsmentioning
confidence: 99%
“…A distinction of scrap tire chips into different sizes and shapes can be found in Bernal-Sanchez (2020), based on ASTM D6270. Numerous studies have demonstrated that when the waste tires are added in the sand as tire derived aggregate (tire chips or shreds), the overall shear strength of the mixture can increase for up to certain tire ratio, which in most cases is below 30% (Edil and Bosscher 1994;Foose et al 1996;Tatlisoz et al 1998;Wu et al 2002;Zornberg et al 2004;Ghazavi and Sakhi 2005;Attom 2006;Rao and Dutta 2006;Kim and Santamarina 2008;Edincliler et al 2010;Cabalar 2011;Mohamad et al 2013;Balunaini et al 2014;Fu et al 2014;Mashiri et al 2015). However, when the tires are used as particulate rubber (crumbs), it has been observed that the shear strength of the mixture drops (Masad et al 1996;Youwai and Bergado 2003;Sheikh et al 2012;Pasha et al 2019;Tasalloti et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of tire-derived materials into the soil has been the focus of several studies, such as reinforcement for road subsoil or as a component of fill material (Bosscher et al, 1997;Edinçliler & Cagatay, 2013), light fill material for containment structures (Reddy & Krishna, 2017;Moghadam et al, 2018), or as an asphalt additive (Xu et al, 2017), due not only to the potential for finding an adequate destination for waste tires, but also because of the characteristics that these materials provide to the soil. Experimental results reported in the literature show that there are improvements to physical properties and to the tensionstrain behavior of soils that have been reinforced with pneumatic waste material (Ozkul & Baykal, 2007;Tafreshi et al, 2012;Balunaini et al, 2014;Fu et al, 2014;Anvari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%